Role of Natural Gas in Producing Electricity in Afghanistan - Aslami, Alyas (International Journal of Multidisciplinary Approach Research and Science, 2024)
This article depicts the role of natural gas reserves in Afghanistan in the production of electricity in the country. Also, this study estimates the impacts of electricity generation from natural gas on imported electricity. Afghanistan has 62nd position in the world's gas reserves, 79th position in the production of natural gas, and 104th position in the consumption of natural gas. Afghanistan has 1,750,000 million cubic feet of natural gas reserves, 6,675 million cubic feet of production of natural gas per year, and 5,163 million cubic feet of consumption of natural gas per year. Afghanistan's position in imports and exports of natural gas is zero in the world. Afghanistan’s natural gas reserves are 16.2 trillion cubic feet, located in the northern Amu-Darya and Afghan-Tajik regions, and they can respond to the energy demand of Afghanistan’s people. At present, the imports of electricity from neighboring countries are 4,900 GWh per year. To carry out this study, we have used secondary data that was collected from reliable academic sources. Descriptive analysis and a quantitative approach are used for analyzing the data. The result shows that electricity generation from the natural gas reserves of Afghanistan is 1,260.45 GWh per year. This amount can reduce the imported electricity from 4,900 GWh to 2,592.55 GWh.